2022
DOI: 10.1007/s10238-022-00911-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cancer on the severity of disease in patients affected with COVID-19: an umbrella review and meta-meta-analysis of systematic reviews and meta-analyses involving 1,064,476 participants

Abstract: During the COVID-19 pandemic, cancer patients were among the most vulnerable patient groups to the SARS-CoV-2 infection effects. This paper aimed to conduct an umbrella review and meta-meta-analysis to determine the severity of disease in cancer patients affected by COVID-19. The umbrella review and meta-meta-analysis were undertaken according to the PRISMA and MOOSE guidelines. The PubMed/Medline, Web of Science, and Scopus databases were searched for published papers from the start of the pandemic through Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The quality of meta-analyses was evaluated utilizing the 16-item AMSTAR-2 (A Mea-Surement Tool to Assess Systematic Reviews) tool (Table S3) [28]. Seven of the sixteen items in AMSTAR-2 were classified as crucial items (items 2,4,7,9,11,13,15). AMSTAR-2 has been defined as an evaluation tool, developed to enable the evaluation of systematic reviews of randomized and non-randomized studies of health interventions.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of meta-analyses was evaluated utilizing the 16-item AMSTAR-2 (A Mea-Surement Tool to Assess Systematic Reviews) tool (Table S3) [28]. Seven of the sixteen items in AMSTAR-2 were classified as crucial items (items 2,4,7,9,11,13,15). AMSTAR-2 has been defined as an evaluation tool, developed to enable the evaluation of systematic reviews of randomized and non-randomized studies of health interventions.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Cancer, which is a complicated group of malignant disorders characterized by abnormal cell proliferation and an uncontrolled cell cycle, remains a major cause of death globally, regardless of human development levels, in countries all over the world [ 1 , 2 , 3 , 4 ]. According to Global Cancer Observatory (GLOBOCAN) data, approximately 19.3 million new cancer cases were reported, and 10 million deaths were attributed to cancer worldwide in 2020 [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer, which comprises a diverse set of diseases characterized by irregular cell proliferation and an unregulated cell cycle, remains a major cause of death globally, regardless of human development levels in countries all over the world [1][2][3][4]. According to Global Cancer Observatory (GLOBOCAN) data, approximately 19.3 million new cancer cases were reported, and 10 million deaths were attributed to cancer worldwide in 2020 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Two umbrella reviews and meta-analyses on the association between pre-existing health conditions and severe outcomes from COVID-19 have shown that other than diabetes, obesity, heart failure, chronic obstructive pulmonary disease and dementia, active cancer was also linked with a higher risk of death, particularly in Europe and North America [ 22 , 23 ]. Oncologic patients may be more susceptible to SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…Evidence is mixed regarding COVID-19 severity in cancer patients [ 24 , 25 , 26 ], while COVID-19 outcomes in these patients are improved with an earlier diagnosis, the availability of effective COVID-19 vaccines, the advent of the omicron outbreak and the timely use of anti-viral therapy [ 24 , 27 ]. Despite all the abovementioned factors, most studies have highlighted an elevated risk of severe COVID-19 in patients with active cancer, particularly in non-vaccinated individuals [ 22 , 23 , 25 , 28 , 29 ]. The risk may vary by type and stage of cancer and treatment.…”
mentioning
confidence: 99%